2015
DOI: 10.1128/jvi.03029-14
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of Pathogenic Events in Cynomolgus Macaques Infected with Aerosolized Monkeypox Virus

Abstract: To evaluate new vaccines when human efficacy studies are not possible, the FDA's "Animal Rule" requires well-characterized models of infection. Thus, in the present study, the early pathogenic events of monkeypox infection in nonhuman primates, a surrogate for variola virus infection, were characterized. Cynomolgus macaques were exposed to aerosolized monkeypox virus (10 5 PFU). Clinical observations, viral loads, immune responses, and pathological changes were examined on days 2, 4, 6, 8, 10, and 12 postchall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…Because the intent is to replicate severe disease, MPXV infection studies using NHPs are rarely performed with low-dose virus challenge, and the dose required for successful infection can vary between different species of host. Both observational and experimental studies suggest that dose influences not only illness severity, but also the length of incubation period and the manifestations of illness in NHPs and in humans [ 42 , 55 , 56 ]. Respiratory challenge at high doses generally results in compressed incubation periods and respiratory syndromes and as such may have more bearing on the clinical picture of persons affected during MPX outbreaks during periods of significant inter-human transmission (i.e., transmission through respiratory routes).…”
Section: Discussionmentioning
confidence: 99%
“…Because the intent is to replicate severe disease, MPXV infection studies using NHPs are rarely performed with low-dose virus challenge, and the dose required for successful infection can vary between different species of host. Both observational and experimental studies suggest that dose influences not only illness severity, but also the length of incubation period and the manifestations of illness in NHPs and in humans [ 42 , 55 , 56 ]. Respiratory challenge at high doses generally results in compressed incubation periods and respiratory syndromes and as such may have more bearing on the clinical picture of persons affected during MPX outbreaks during periods of significant inter-human transmission (i.e., transmission through respiratory routes).…”
Section: Discussionmentioning
confidence: 99%
“…Various models have been established throughout the years in various hosts. Non-human primates develop severe disease with disseminated lesions and death, following respiratory infections, yet a rather high dose of MPXV (doses of >10 6 pfu) is usually needed to produce acute severe systemic disease [ 96 , 97 , 98 ]. This potential disadvantage of the non-human primate model and the inherent complexities of working with NHPs led to the development of MPXV models in small animal species, including prairie dogs, squirrels, African dormice, Gambian rats, and selected mouse strains with attenuated immune response [ 17 , 99 , 100 , 101 , 102 , 103 , 104 ].…”
Section: Animal Modelsmentioning
confidence: 99%
“…A recent study also evaluated the cytokine levels in aerosol challenged animals. (Tree et al, 2015). Tree et al (2015) showed that IFNγ, Il-1rα, and Il-6 increased dramatically on day 8 postexposure the day that death was most likely to occur, and viral DNA was detected in most of the tissues.…”
Section: Monkeypox Virusmentioning
confidence: 99%
“…(Tree et al, 2015). Tree et al (2015) showed that IFNγ, Il-1rα, and Il-6 increased dramatically on day 8 postexposure the day that death was most likely to occur, and viral DNA was detected in most of the tissues. These results support the idea of a cytokine storm causing mortality in monkeypox disease.…”
Section: Monkeypox Virusmentioning
confidence: 99%